Controversies and present challenges of patenting Antarctic bio-resources - Sepúlveda Illanes, Catalina (Universidad de Chile. Facultad de Derecho, 2019)
Bioprospecting is a relevant scientific activity in Antarctica but it is also an economical important issue. However, from the Antarctic Treaty System point of view and the Antarctic resources exploitation there are several issues not resolved. One of this matter is the patenting of Antarctic bio-resources. La bioprospección es una actividad científica relevante en la Antártica, pero también de importancia económicas. Sin embargo, desde la perspectiva del Sistema del Tratado Antártico y del uso de los recursos antárticos existen una serie de cuestiones no resultas. Una de ellas es la referida a la patentabilidad de los bio-recursos antárticos.